Factors Influencing Online Shopping Behavior of Customers: A Case Study of an E-Commerce Platform - Tick Ying Heng; Rui Sin Ho; Herasiny A/P Pushpanathan; An Yuan Hu (AIBPM Publisher, 2024)
As time goes by, the advancement of technology has brought tremendous impact to all fields. Consumers’ purchasing behavior has changed due to the existence of e-commerce. This study aims to examine the factors influencing online shopping behavior by conducting a case study on Shopee. This study was carried out through data collection by using a survey questionnaire and secondary data analysis and collection obtained from other sources such as online related websites. There were 150 Shopee users who responded to the survey. The results indicated that perceived convenience emerged as the strongest predictor (? = 0.457), followed by perceived ease of use (? = 0.280) and perceived trust (? = 0.250). Interestingly, perceived usefulness was not found to be a significant factor (? = -0.055). These findings suggest that online businesses should prioritize convenience, user experience (UX) design, and trust-building strategies. Further research could explore the reasons behind the unexpected usefulness result and cultural influences on online shopping behavior.